An Ethnographic Inquiry of the Reasons and Factors Behind Ayurvedic Healing Practices - Gautam, Sahadev (Innovative Research Journal, 2023)
Health is a fundamental right of people. The health system is better for the treatment is determined by people’s perceptions by choosing the sources of healing. This paper mainly concerns the patients of Ayurveda and their trust in Ayurveda healing. This paper reveals the reason why patients like to heal with Ayurveda. A qualitative research paradigm has been used to collect data from the grassroots. Case studies and interview methods were used for the interpretation. Nowadays Ayurvedic healing is popular with many people. Also, in pursuit of finding better health care patients used to take healing from Ayurveda as an alternative medicine. From the research, all respondents considered many reasons to select Ayurvedic. Expensive allopathic medicine and many side effects are the major factors for Ayurvedic healing practice at the same time patients believe in fewer side effects of Ayurveda. Now the health care system is guided by a capitalistic school of thought. The healthcare delivery system in many countries, including Nepal is changing.